Ultra-low internal stress high entropy flexible composite film and preparation method and preparation device thereof
By adopting a winding composite ion beam processing device and gradient nano multilayer structure design in the energy-carrying ion beam technology, combined with the ultra-low duty cycle and high bias voltage pulse deposition strategy, an ultra-low internal stress high-entropy flexible composite film was successfully prepared, solving the problem of high internal stress in the energy-carrying ion beam technology, and realizing the preparation of high-quality flexible high-entropy thin films.
Patent Information
- Application Number
- CN202411919957.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
The application of energy-carrying ion beam technology in the field of flexibility is limited by the high internal stress problems caused by energy-carrying ion deposition, which leads to film failures such as layering, microcracks, wrinkles and shedding.
Using a winding composite ion beam treatment device, ultra-low internal stress high entropy flexible composite film is prepared through gradient nano-multilayer structure design and ultra-low duty cycle high bias pulse deposition strategy. The method includes alternately depositing a high entropy alloy buffer layer and a high entropy oxide barrier layer on a polymer substrate, and reducing the internal stress of the film using ultra-low duty cycle high bias pulse technology.
Low internal stress, high bonding strength, low deposition temperature, high film density and high deposition rate are achieved, significantly improving the water-oxygen barrier performance of polymer films and greatly improving mechanical properties.
Smart Images

Figure CN119736599A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of film preparation, and in particular relates to an ultra-low internal stress high entropy flexible composite film and a preparation method and a preparation device thereof. Background Art
[0002] Energetic ion beam technology can quickly prepare high-density and high-entropy films at low temperatures, but it has not been widely used in the flexible field. One of the main reasons is the high internal stress of the film caused by energetic ion deposition. According to the direction of film stress, internal stress can be divided into compressive stress and tensile stress. If the film has a tendency to expand on the surface of the substrate, compressive stress will be formed, and compressive stress is usually expressed as a negative number. On the contrary, if the film has a tendency to shrink along the surface of the substrate, tensile stress is formed, and tensile stress is usually expressed as a positive number. When the growing film is bombarded by ions with an energy of tens or hundreds of eV, the energetic ions enter the already grown film as foreign atoms, causing the film to tend to expand outward from the substrate, generating macroscopic compressive stress. Although energetic ion bombardment is also conducive to the formation of dense films, excessive film internal stress can cause film failure. When there is a strong adhesion between the substrate and the film, excessive tensile stress will cause the film to delaminate or produce microcracks; when there is a large compressive stress inside the film, the film will wrinkle or fall off, which often causes the film to buckle on a macro scale. This greatly limits the practical application of energetic ion beam technology in the flexible field.
[0003] The internal stress of the film can be divided into thermal stress and intrinsic stress, and the internal stress of the film is the sum of the two. The thermal stress of the film is caused by the difference in thermal expansion coefficient between the film and the substrate. When the substrate and the film are cooled, the difference in thermal expansion coefficient will cause the two to shrink inconsistently. If the thermal expansion coefficient of the substrate is smaller than that of the film material, tensile stress will be formed, and vice versa, compressive stress will be formed. The source of the intrinsic stress of the film is very complicated. This is mainly because the growth of the film is a dynamic process. The stress generation mechanism will be different at different stages of film formation, and different film formation methods will also make the stress generation mechanism different. Therefore, to understand the specific cause of the internal stress of the film, it is necessary to dynamically observe the stress accumulation process from a microscopic perspective, which requires extremely high experimental conditions and is often difficult to achieve. In terms of theoretical models, researchers have summarized some causes of intrinsic stress, mainly impurity effects, atomic shot peening effects, lattice mismatch, grain boundary elimination and other theories. In order to reduce the internal stress of the film and avoid film failure, the stress elimination strategies currently developed mainly include thermal annealing, multilayer structure design, parameter optimization and element doping.
[0004] The above stress relief methods have been widely used in the field of thin films to improve the quality of thin films. However, for polymer substrates and devices that are highly sensitive to temperature, most internal stress relief methods are not applicable. For example, polyethylene naphthalate (PEN), a common thin film encapsulation polymer material in the OLED field, can only withstand a temperature of about 160°C, and the common green light-emitting material 8-hydroxyquinoline aluminum (Alq3) will significantly reduce its fluorescence intensity at 200°C; and the temperature resistance of common electronic devices in the IC field is only around 100°C. In addition, when a flexible organic substrate is used as a substrate, due to the large difference in thermal expansion coefficients between the inorganic film and the organic substrate, heat treatment may cause greater thermal stress in the film, so high-temperature heat treatment processes are not applicable.
[0005] Although some studies have shown that increasing the working gas pressure can effectively reduce the internal stress of the film, it may also reduce the film density and deposition rate, significantly affecting the overall performance and preparation efficiency of the film. Some research reports also show that the internal stress of the film can be reduced by increasing the negative bias voltage of the deposition, but the excessively high duty cycle of the traditional negative bias power supply often causes the substrate temperature to rise, which also has a negative impact. The method of eliminating internal stress by doping impurity elements may change the performance of the film in other aspects, such as reduced transmittance, increased roughness, reduced hardness, etc.
[0006] Therefore, exploring a new low-temperature internal stress elimination method that has no significant effect on other properties of the film is the key to fully utilizing the advantages of energetic ion beam deposition technology to achieve the preparation of high-quality flexible high-entropy films with low deposition temperature, high film density, high deposition rate, low film internal stress and high bonding strength. Summary of the invention
[0007] In view of this, the present invention discloses an ultra-low internal stress high-entropy flexible composite film and a preparation method and a preparation device thereof. The flexible composite film prepared by this technology has extremely high surface flatness, extremely low residual stress and excellent interface adhesion strength, which can effectively alleviate the local curling, debonding and cracking of the high-entropy composite film, and greatly improve the mechanical properties of polymer parts.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] A device for preparing an ultra-low internal stress high entropy flexible composite film, the film preparation device is a winding composite ion beam processing device, the film is driven by a guide roller from front to back through a Kaufman ion source etching system, a MEVVA ion co-injection system, a magnetic filtration cathode vacuum arc co-deposition system, and an ultra-low duty cycle high bias pulse magnetic filtration cathode vacuum arc co-deposition system.
[0010] Preferably, an isolation chamber is provided between adjacent systems in the Kaufman ion source etching system, the MEVVA ion co-injection system, the magnetic filtration cathode vacuum arc co-deposition system, and the ultra-low duty cycle high bias pulse magnetic filtration cathode vacuum arc co-deposition system; and an extreme cooling system is provided in the isolation chamber;
[0011] The MEVVA ion co-injection system, the magnetic filtration cathode vacuum arc co-deposition system, and the ultra-low duty cycle high bias pulse magnetic filtration cathode vacuum arc co-deposition system are all provided with a deep cooling system.
[0012] Preferably, the Kaufman ion source etching system, the MEVVA ion co-injection system, the magnetic filtration cathode vacuum arc co-deposition system, and the ultra-low duty cycle high bias pulse magnetic filtration cathode vacuum arc co-deposition system are all provided with a molecular pump for vacuuming.
[0013] The present invention also discloses a method for preparing an ultra-low internal stress high entropy flexible composite film, which is prepared by using the above-mentioned preparation device and specifically comprises the following steps:
[0014] S01: Degas the polymer substrate using an oven, then place it into the vacuum chamber of the Kaufman ion source etching system and start the unwinding process;
[0015] S02: Use the Kaufman ion source etching system to perform low-energy small-beam etching on the polymer substrate;
[0016] S03: Use the MEVVA ion co-implantation system to perform medium energy and high beam current metal ion implantation on the etched polymer substrate;
[0017] S04: Depositing a high entropy alloy buffer layer on the surface of a polymer substrate after metal ion implantation using a magnetically filtered cathode vacuum arc co-deposition system;
[0018] S05: Deposition of high entropy oxide barrier layer on the surface of high entropy alloy buffer layer on polymer substrate using ultra-low duty cycle high bias pulsed magnetic filtered cathodic vacuum arc co-deposition system;
[0019] S06: S04 and S05 are cycled alternately for multiple times, the deposition parameters of each layer of the S04 high entropy alloy buffer layer remain unchanged, and the oxygen flux of each layer of the S05 high entropy oxide barrier layer increases;
[0020] S07: Collect the papers.
[0021] Preferably, the degassing temperature in S01 is 80-120°C, and the thickness of the polymer substrate is 6-120 μm;
[0022] The parameters of the low-energy small beam etching described in S02 are: ion energy 200-1000eV, beam intensity 5-85mA; etching temperature 40-80°C, reaction gas Ar, O2 or N2, etching speed 3-10m·min -1 , the surface roughness after etching is between 400-850nm.
[0023] Preferably, the parameters of the large beam metal ion implantation in S03 are: ion energy 5-20keV, beam intensity 2-8mA; processing speed 3-10m·min -1 The treatment dose was 10 15 -10 16 atoms·cm -2 After injection, the metal element content of the polymer base layer within 25nm is not less than 2.5%, and the defect density is not less than 10 16 cm -3 The injected metals are Ni, Cr, and Cu, and the ratio is (3-4): (0-2): (0-2).
[0024] Preferably, the co-deposition parameters of S04 are: arc discharge current 70-130A, pulse magnetic field current 5-30A, pulse frequency 10-100Hz; substrate negative bias 0-400V; deposition thickness 3-15nm.
[0025] Preferably, the co-deposition parameters of S05 are: arc discharge current 70-130A, pulse magnetic field current 5-30A, magnetic field pulse frequency 10-100Hz; substrate negative bias 0-9kV, bias pulse width 4μs, peak pulse width 1μs, bias pulse frequency 10-50Hz, bias duty cycle reaches 0.2‰-1‰; oxygen flux 0-80sccm; deposition thickness 15-30nm;
[0026] In S06, S04 and S05 are cycled alternately for 5-10 times, and the oxygen flux deposited in each layer of the S05 high entropy oxide barrier layer increases in an arithmetic progression.
[0027] The ultra-low internal stress high entropy flexible composite film prepared by the above preparation method includes, from bottom to top, a polymer substrate, a high entropy ion pinning mixed layer, and a highly flexible high entropy alloy buffer layer and a low stress gradient high entropy oxide barrier layer alternately deposited on the surface of the high entropy ion pinning mixed layer.
[0028] It can be seen from the above technical solutions that compared with the prior art, the present invention has the following excellent effects:
[0029] The traditional film stress elimination process may damage the substrate or device life, generate large film base thermal stress, sacrifice film density and deposition speed; leading to problems such as reduced film transmittance, increased roughness, and reduced hardness. The present invention designs a winding composite ion beam processing device, and adopts a gradient nano-multilayer structure design and an ultra-low duty cycle high bias pulse deposition deposition strategy to achieve low film internal stress, high bonding strength, low deposition temperature, high film density, and high deposition rate. High-quality flexible high-entropy composite film preparation, and greatly improves the water and oxygen barrier properties of polymer films. The preparation method of the present invention has high efficiency, large width (up to 1m), low cost, and a travel speed of 4-12m·min. -1 .
[0030] The flexible composite film prepared by the present invention has the following properties:
[0031] 1. The prepared high entropy composite film has high overall flatness and internal stress is less than -86MPa (residual stress is calculated by the film curvature radius);
[0032] 2. The prepared high entropy composite film has high interface adhesion strength, which can reach 1.5N·mm -1 (45° peel test);
[0033] 3. The prepared composite film has good water and oxygen barrier properties, and the water vapor transmission rate can be as low as 4.6×10 -6 g·m -2 ·day -1 (Metal corrosion test);
[0034] 4. The preparation temperature is less than 50°C, and the film bulk density can reach 0.9786 (the bulk density is calculated by the film refractive index). BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0036] Figure 1 It is a schematic diagram of a preparation device for an ultra-low internal stress high entropy flexible composite film of the present invention;
[0037] Figure 2 This is a cross-sectional SEM image of the high entropy flexible composite film prepared in Example 1 of the present invention.
[0038] exist Figure 1 middle,
[0039] 201 observation window, 202 unwinding roller, 203 molecular pump, 204 Kaufman ion source etching system, 205 guide roller, 206 MEVVA ion co-injection system, 207 magnetic filtration cathode vacuum arc co-deposition system, 208 ultra-low duty cycle high bias pulse magnetic filtration cathode vacuum arc co-deposition system, 209 deep cooling system, 210 isolation chamber. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] S01 Unwinding
[0042] The polymer is degassed in an oven at a temperature of 80-120°C, placed in a vacuum chamber, and unwinding is started;
[0043] S02 Kaufman ion source etching system;
[0044] The polymer substrate was etched with low energy and small beam current using the Kaufman ion source system. The ion energy was 200-1000eV, the beam current was 5-85mA, the etching temperature was 40-80℃, the reaction gas was Ar, O2, N2, etc., and the etching speed was 3-10m·min -1 , the surface roughness after etching is 400-850nm;
[0045] S03 MEVVA ion co-implantation system;
[0046] The MEVVA ion implantation system is used to implant medium energy and high current metal ions into polymer matrix; ion energy 5-20keV, beam intensity 2-8mA; processing speed 3-10m·min -1 , the treatment dose is 1015-1016atoms cm -2 After injection, the metal element content of the polymer subsurface within 25nm is not less than 2.5%, and the defect density is not less than 1016cm -3 ;
[0047] S04 magnetic filtration cathode vacuum arc co-deposition system;
[0048] A high entropy alloy buffer layer is deposited on the surface of a polymer matrix using a magnetically filtered cathode vacuum arc co-deposition system; high-throughput energetic ion beam technology can achieve customized construction and regulation of the material surface / interface composition, structure, and function. Due to its advantages such as high ionization rate and high plasma density, it can achieve wide-range regulation of incident energy and flux, significantly enhance the atomic mobility on the surface of the crystal core, and is suitable for the deposition of high-density nanocrystalline films on low-thermal budget substrates such as flexible polymers. With the introduction of co-deposition technology, the design and regulation of low-cost high-entropy films has gradually become possible. Multi-channel design can achieve independent regulation of components and phase structures in high-entropy films and inhibit phase separation under low-temperature conditions.
[0049] During the deposition process, the arc discharge current is 70-130A, the pulse magnetic field current is 5-30A, the pulse frequency is 10-100Hz; the substrate negative bias voltage is 0-400V; and the deposition thickness is 3-15nm.
[0050] S05 ultra-low duty cycle high bias pulse magnetic filter cathode vacuum arc co-deposition system;
[0051] The high entropy oxide barrier layer is deposited using an ultra-low duty cycle high bias pulse magnetic filtered cathode vacuum arc co-deposition system; the peak voltage of the traditional negative bias power supply is often low (0-1000V). In order to give the atoms on the surface of the film enough kinetic energy to eliminate internal defects, a higher duty cycle (20%-100%) is usually required. Under such a high duty cycle, the high-energy ion beam continuously bombards the surface of the film growth, inevitably causing the deposition temperature to rise, causing damage to the flexible organic substrate and electronic devices. The ultra-low duty cycle (0.2‰) high bias pulse technology has a higher peak voltage (0-9kV), which can give the deposited ions enough kinetic energy, and has a longer "empty" time, which can fully cool the deposited film. In addition, the longer "empty" time can also allow the electrons in the plasma to reach the substrate to neutralize the positive charge, effectively avoiding arc breakdown caused by charging on the surface of the insulating substrate.
[0052] During the deposition process, the arc discharge current is 70-130A, the pulse magnetic field current is 5-30A, and the magnetic field pulse frequency is 10-100Hz; the substrate negative bias is 0-9kV, the bias pulse width is 4μs, the peak pulse width is 1μs, the bias pulse frequency is 10-50Hz, and the bias duty cycle reaches 0.2‰-1‰; the oxygen flux is 0-80sccm; and the deposition thickness is 15-30nm.
[0053] S06 Cycle
[0054] S04 and S05 were deposited in cycles for a total of X times.
[0055] S07 Rolling
[0056] After the treatment is completed, the polymer is wound up for treatment.
[0057] Example 1
[0058] S01 Unwinding
[0059] The polymer substrate PEN film (thickness 50 μm) was degassed in an oven at a treatment temperature of 80°C, placed in a vacuum chamber, and started unwinding treatment;
[0060] S02 Kaufman ion source etching;
[0061] The polymer substrate was etched with low energy and small beam current using a Kaufman ion source etching system. The ion energy was 300 eV, the beam current was 25 mA, the etching temperature was 45 °C, the reaction gas was Ar, and the etching speed was 5 m / min. -1 , the surface roughness after etching is 450nm;
[0062] S03 MEVVA ion co-implantation;
[0063] The MEVVA ion implantation system was used to implant medium energy and high current metal ions into polymer substrates; the acceleration voltage was 9 kV, the beam current was 3.5 mA, and the processing speed was 5 m·min -1 , treatment dose 5×10 15 atoms cm -2 After injection, the metal element content of the polymer subsurface within 25nm is 3.5%, and the defect density is about 1.5×10 16 cm -3 , injection speed 4m·min -1 , the injected metals are Ni, Cr, and Cu, with a molar ratio of 3:1:2;
[0064] S04 magnetic filtration cathode vacuum arc co-deposition;
[0065] TiAlCrZrSi high entropy alloy buffer layer was deposited on the polymer substrate surface using a magnetic filtered cathode vacuum arc co-deposition system. During the deposition process, the arc discharge current was 90-120A, the pulse magnetic field current was 25A, and the pulse frequency was 50Hz. The substrate negative bias voltage was 100V. The deposition speed was 4m·min -1 , deposition thickness 5nm;
[0066] S05 ultra-low duty cycle high bias pulsed magnetic filtered cathode vacuum arc co-deposition;
[0067] Ultra-low duty cycle high bias pulsed magnetic filtered cathodic vacuum arc co-deposition system for (TiAlCrZrSi)O xBarrier layer deposition; during deposition, arc discharge current was 90-120A, pulse magnetic field current was 25A, and magnetic field pulse frequency was 80Hz; substrate negative bias voltage was 7kV, bias pulse width was 4μs, peak pulse width was 1μs, bias pulse frequency was 50Hz, and bias duty cycle reached 0.2‰; oxygen flux was 5-50sccm, and oxygen gradient increment was 5sccm / cycle; deposition speed was 4m·min -1 ; Deposition thickness 15nm.
[0068] S06 Cycle
[0069] S04 and S05 were deposited 10 times in total (Note: the deposition parameters of each layer of high entropy alloy deposition remain unchanged, and the oxygen flux of high entropy oxide deposition increases, namely 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 sccm, for a total of 10 layers), with a total thickness of 200 nm and an equiaxed crystal structure;
[0070] S07 Rolling
[0071] After the treatment, the polymer was rolled up and the residual stress of the composite film was -70MPa, and the bulk density was 0.9987; the interface adhesion strength between the high entropy film and the polymer substrate was about 1.5N·mm -1 ; Water vapor transmission rate is 4.6×10 -6 g·m -2 ·day -1 .
[0072] Example 2 (Oxygen gradient change)
[0073] S01 Unwinding
[0074] The PEN film (thickness 50 μm) was degassed in an oven at a temperature of 80°C, placed in a vacuum chamber, and unwinding was started;
[0075] S02 Kaufman ion source etching;
[0076] The polymer substrate was etched with low energy and small beam current using a Kaufman ion source etching system. The ion energy was 300 eV, the beam current was 25 mA, the etching temperature was 45 °C, the reaction gas was Ar, and the etching speed was 5 m / min. -1 , the surface roughness after etching is 450nm;
[0077] S03 MEVVA ion co-implantation;
[0078] The MEVVA ion implantation system was used to implant medium energy and high current metal ions into polymer substrates; the acceleration voltage was 9 kV, the beam current was 3.5 mA, and the processing speed was 5 m·min -1 , treatment dose 5×10 15atoms cm -2 After injection, the metal element content of the polymer subsurface within 25nm is 3.5%, and the defect density is about 1.5×10 16 cm -3 , injection speed 4m·min -1 , the injected metals are Ni, Cr, and Cu, with a molar ratio of 3:1:2;
[0079] S04 magnetic filtration cathode vacuum arc co-deposition;
[0080] TiAlCrZrSi high entropy alloy buffer layer was deposited on the polymer substrate surface using a magnetic filtered cathode vacuum arc co-deposition system. During the deposition process, the arc discharge current was 90-120A, the pulse magnetic field current was 25A, and the pulse frequency was 50Hz. The substrate negative bias voltage was 100V. The deposition speed was 4m·min -1 , deposition thickness 5nm;
[0081] S05 ultra-low duty cycle high bias pulsed magnetic filtered cathode vacuum arc co-deposition;
[0082] Ultra-low duty cycle high bias pulsed magnetic filtered cathodic vacuum arc co-deposition system for (TiAlCrZrSi)O x Barrier layer deposition; during deposition, arc discharge current was 90-120A, pulse magnetic field current was 25A, and magnetic field pulse frequency was 80Hz; substrate negative bias voltage was 7kV, bias pulse width was 4μs, peak pulse width was 1μs, bias pulse frequency was 50Hz, and bias duty cycle reached 0.2‰; oxygen flux was 0-72sccm, and oxygen gradient increment was 8sccm / cycle; deposition speed was 4m·min -1 ; Deposition thickness 15nm.
[0083] S06 Cycle
[0084] S04 and S05 were deposited 10 times in total (Note: the deposition parameters of each layer of high entropy alloy deposition remain unchanged, and the oxygen flux of high entropy oxide deposition increases, which are 0, 8, 16, 24, 32, 40, 48, 56, 64, and 72 sccm, respectively, for a total of 10 layers), with a total thickness of 200 nm and an equiaxed crystal structure;
[0085] S07 Rolling
[0086] After the treatment, the polymer was rolled up and the residual stress of the composite film was -96MPa, and the bulk density was 0.9260; the interface adhesion strength between the high entropy film and the polymer substrate was about 1.4N·mm -1 ; Water vapor transmission rate is 8.1×10 -6 g·m -2 ·day -1 .
[0087] Example 3 (Duty Cycle Variation)
[0088] S01 Unwinding
[0089] The polymer substrate PEN film (thickness 50 μm) was degassed in an oven at a treatment temperature of 80°C, placed in a vacuum chamber, and started unwinding treatment;
[0090] S02 Kaufman ion source etching;
[0091] The polymer substrate was etched with low energy and small beam current using a Kaufman ion source etching system. The ion energy was 300 eV, the beam current was 25 mA, the etching temperature was 45 °C, the reaction gas was Ar, and the etching speed was 5 m / min. -1 , the surface roughness after etching is 450nm;
[0092] S03 MEVVA ion co-implantation;
[0093] The MEVVA ion implantation system was used to implant medium energy and high current metal ions into polymer substrates; the acceleration voltage was 9 kV, the beam current was 3.5 mA, and the processing speed was 5 m·min -1 , treatment dose 5×10 15 atoms cm -2 After injection, the metal element content of the polymer subsurface within 25nm is 3.5%, and the defect density is about 1.5×10 16 cm -3 , injection speed 4m·min -1 , the injected metals are Ni, Cr, and Cu, with a molar ratio of 3:1:2;
[0094] S04 magnetic filtration cathode vacuum arc co-deposition;
[0095] TiAlCrZrSi high entropy alloy buffer layer was deposited on the polymer substrate surface using a magnetic filtered cathode vacuum arc co-deposition system. During the deposition process, the arc discharge current was 90-120A, the pulse magnetic field current was 25A, and the pulse frequency was 50Hz. The substrate negative bias voltage was 100V. The deposition speed was 4m·min -1 , deposition thickness 5nm;
[0096] S05 ultra-low duty cycle high bias pulsed magnetic filtered cathode vacuum arc co-deposition;
[0097] Ultra-low duty cycle high bias pulsed magnetic filtered cathodic vacuum arc co-deposition system for (TiAlCrZrSi)O xBarrier layer deposition; during deposition, arc discharge current was 90-120A, pulse magnetic field current was 25A, and magnetic field pulse frequency was 80Hz; substrate negative bias voltage was 7kV, bias pulse width was 4μs, peak pulse width was 1μs, bias pulse frequency was 10Hz, and bias duty cycle reached 1‰; oxygen flux was 5-50sccm, and oxygen gradient increment was 5sccm / cycle; deposition speed was 4m·min -1 ; Deposition thickness 15nm.
[0098] S06 Cycle
[0099] S04 and S05 were deposited 10 times in total (Note: the deposition parameters of each layer of high entropy alloy deposition remain unchanged, and the oxygen flux of high entropy oxide deposition increases, namely 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 sccm, for a total of 10 layers), with a total thickness of 200 nm and an equiaxed crystal structure. The higher the oxygen flux, the higher the hardness of the film, the worse the toughness, and the improved barrier performance.
[0100] S07 Rolling
[0101] After the treatment, the polymer was rolled up and the residual stress of the composite film was -258MPa, and the bulk density was 0.9989; the interface adhesion strength between the high entropy film and the polymer substrate was about 1.6N·mm -1 ; Water vapor transmission rate is 1.03×10 -5 g·m -2 ·day -1 .
[0102] Compared with Example 1, it can be seen that a decrease in the duty cycle of the bias pulse will lead to an increase in the residual stress of the composite film, a decrease in the toughness of the film and an easy cracking, thereby causing a significant increase in the water vapor permeability.
[0103] Example 4
[0104] S01 Unwinding
[0105] The polymer substrate PEN film (thickness 50 μm) was degassed in an oven at a treatment temperature of 120°C, placed in a vacuum chamber, and started unwinding treatment;
[0106] S02 Kaufman ion source etching;
[0107] The polymer substrate was etched with a low-energy small beam using a Kaufman ion source etching system. The ion energy was 200 eV, the beam intensity was 30 mA, the etching temperature was 40 °C, the reaction gas was O2, and the etching speed was 5 m / min. -1 , the surface roughness after etching is 1250nm;
[0108] S03 MEVVA ion co-implantation;
[0109] The MEVVA ion implantation system was used to implant medium energy and high current metal ions into polymer substrates; the acceleration voltage was 9 kV, the beam current was 3.5 mA, and the processing speed was 5 m·min -1 , treatment dose 5×10 15 atoms cm -2 After injection, the metal element content of the polymer subsurface within 25nm is 3.5%, and the defect density is about 1.5×10 16 cm -3 , injection speed 4m·min -1 , the injected metals are Ni, Cr, and Cu, with a molar ratio of 3:1:2;
[0110] S04 magnetic filtration cathode vacuum arc co-deposition;
[0111] TiAlCrZrSi high entropy alloy buffer layer was deposited on the polymer substrate surface using a magnetic filtered cathode vacuum arc co-deposition system. During the deposition process, the arc discharge current was 90-120A, the pulse magnetic field current was 25A, and the pulse frequency was 50Hz. The substrate negative bias voltage was 100V. The deposition speed was 4m·min -1 , deposition thickness 5nm;
[0112] S05 ultra-low duty cycle high bias pulsed magnetic filtered cathode vacuum arc co-deposition;
[0113] Ultra-low duty cycle high bias pulsed magnetic filtered cathodic vacuum arc co-deposition system for (TiAlCrZrSi)O x Barrier layer deposition; during deposition, arc discharge current was 90-120A, pulse magnetic field current was 25A, and magnetic field pulse frequency was 80Hz; substrate negative bias voltage was 7kV, bias pulse width was 4μs, peak pulse width was 1μs, bias pulse frequency was 50Hz, and bias duty cycle reached 0.2‰; oxygen flux was 5-50sccm, and oxygen gradient increment was 5sccm / cycle; deposition speed was 4m·min -1 ; Deposition thickness 15nm.
[0114] S06 Cycle
[0115] S04 and S05 were deposited 10 times in total (Note: the deposition parameters of each layer of high entropy alloy deposition remain unchanged, and the oxygen flux of high entropy oxide deposition increases, namely 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 sccm, for a total of 10 layers), with a total thickness of 200 nm and an equiaxed crystal structure;
[0116] S07 Rolling
[0117] After the treatment, the polymer was rolled up and the residual stress of the composite film was -73MPa, and the bulk density was 0.9674; the interface adhesion strength between the high entropy film and the polymer substrate was about 1.71N·mm -1 ; Water vapor transmission rate is 4.73×10 -6 g·m -2 ·day -1 .
[0118] Compared with Example 1-1, it can be seen that changes in Kaufman etching gas and beam current will lead to increased substrate roughness and decreased composite film stacking density, thereby increasing water vapor permeability.
[0119] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A device for preparing ultra-low internal stress high entropy flexible composite film, characterized in that: The film preparation device is a winding composite ion beam processing device, and the film is driven by a guide roller from front to back through the Kaufman ion source etching system, the MEVVA ion co-injection system, the magnetic filtration cathode vacuum arc co-deposition system, and the ultra-low duty cycle high bias pulse magnetic filtration cathode vacuum arc co-deposition system.
2. A device for preparing ultra-low internal stress high entropy flexible composite film, characterized in that: An isolation chamber is provided between adjacent systems in the Kaufman ion source etching system, the MEVVA ion co-injection system, the magnetic filtration cathode vacuum arc co-deposition system, and the ultra-low duty cycle high bias pulse magnetic filtration cathode vacuum arc co-deposition system; an extreme cooling system is provided in the isolation chamber; The MEVVA ion co-injection system, the magnetic filtration cathode vacuum arc co-deposition system, and the ultra-low duty cycle high bias pulse magnetic filtration cathode vacuum arc co-deposition system are all provided with a deep cooling system.
3. A device for preparing ultra-low internal stress high entropy flexible composite film, characterized in that: The Kaufman ion source etching system, the MEVVA ion co-injection system, the magnetic filtration cathode vacuum arc co-deposition system, and the ultra-low duty cycle high bias pulse magnetic filtration cathode vacuum arc co-deposition system are all provided with a molecular pump for vacuuming.
4. A method for preparing an ultra-low internal stress high entropy flexible composite film, characterized in that: The preparation is carried out using the preparation device according to any one of claims 1 to 3, specifically comprising the following steps: S01: Degas the polymer substrate using an oven, then place it into the vacuum chamber of the Kaufman ion source etching system and start the unwinding process; S02: Use the Kaufman ion source etching system to perform low-energy small-beam etching on the polymer substrate; S03: Use the MEVVA ion co-implantation system to perform medium energy and high beam current metal ion implantation on the etched polymer substrate; S04: Depositing a high entropy alloy buffer layer on the surface of a polymer substrate after metal ion implantation using a magnetically filtered cathode vacuum arc co-deposition system; S05: Deposition of high entropy oxide barrier layer on the surface of high entropy alloy buffer layer on polymer substrate using ultra-low duty cycle high bias pulsed magnetic filtered cathodic vacuum arc co-deposition system; S06: S04 and S05 are cycled alternately for multiple times, the deposition parameters of each layer of the S04 high entropy alloy buffer layer remain unchanged, and the oxygen flux of each layer of the S05 high entropy oxide barrier layer increases; S07: Collect the papers.
5. The method for preparing an ultra-low internal stress high entropy flexible composite film according to claim 4, characterized in that: In S01, the degassing temperature is 80-120°C and the polymer substrate thickness is 6-120 μm; The parameters of the low-energy small beam etching described in S02 are: ion energy 200-1000eV, beam intensity 5-85mA; etching temperature 40-80°C, reaction gas Ar, O2 or N2, etching speed 3-10m·min -1 , the surface roughness after etching is between 400-850nm.
6. The method for preparing an ultra-low internal stress high entropy flexible composite film according to claim 4, characterized in that: The parameters of the large beam metal ion implantation described in S03 are: ion energy 5-20keV, beam intensity 2-8mA; processing speed 3-10m·min -1 The treatment dose was 10 15 -10 16 atoms·cm -2 After injection, the metal element content of the polymer base layer within 25nm is not less than 2.5%, and the defect density is not less than 10 16 cm -3 The injected metals are Ni, Cr, and Cu, and the ratio is (3-4): (0-2): (0-2).
7. The method for preparing an ultra-low internal stress high entropy flexible composite film according to claim 4, characterized in that: Co-deposition parameters in S04: arc discharge current 70-130A, pulse magnetic field current 5-30A, pulse frequency 10-100Hz; substrate negative bias 0-400V; Deposition thickness 3-15nm.
8. The method for preparing an ultra-low internal stress high entropy flexible composite film according to claim 4, characterized in that: Co-deposition parameters in S05: arc discharge current 70-130A, pulse magnetic field current 5-30A, magnetic field pulse frequency 10-100Hz; substrate negative bias 0-9kV, bias pulse width 4μs, peak pulse width 1μs, bias pulse frequency 10-50Hz, bias duty cycle reaches 0.2‰-1‰; oxygen flux 0-80sccm; deposition thickness 15-30nm; In S06, S04 and S05 are cycled alternately for 5-10 times, and the oxygen flux deposited in each layer of the S05 high entropy oxide barrier layer increases in an arithmetic progression.
9. An ultra-low internal stress high entropy flexible composite film prepared according to the preparation method according to any one of claims 4 to 8.
10. The ultra-low internal stress high entropy flexible composite film according to claim 9, characterized in that: The flexible composite film comprises, from bottom to top, a polymer substrate, a high-entropy ion pinning mixed layer, and a highly flexible high-entropy alloy buffer layer and a low-stress gradient high-entropy oxide barrier layer alternately deposited on the surface of the high-entropy ion pinning mixed layer.
Citation Information
Cited By
Plasma etching resistant high-entropy coating as well as preparation method and application thereof
CN120425303A
A plasma etching resistant high entropy coating and its preparation method and application
CN120425303B
Three-dimensional composite current collector and preparation method thereof
CN120432548A
Three-dimensional composite current collector and method for manufacturing the same
CN120432548B